1993
DOI: 10.1177/036354659302100416
|View full text |Cite
|
Sign up to set email alerts
|

High- versus low-top shoes for the prevention of ankle sprains in basketball players

Abstract: Using a prospective, randomized experimental design, 622 college intramural basketball players were stratified by a previous history of ankle sprains to wear a new pair of either high-top, high-top with inflatable air chambers, or low-top basketball shoes during all games for a complete season. Subjects were asked to complete a history questionnaire and were given a complete ankle examination. They were allowed to wear these shoes only during basketball competition. Followed over the course of a 2-month intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
2
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(68 citation statements)
references
References 10 publications
2
56
2
6
Order By: Relevance
“…Dahle et al [14] and Barrett et al. [15] found no correlation between foot type and ankle sprains whereas Williams et al [16] reported a higher incidence of ankle sprains in individuals with a high arch.…”
Section: Introductionmentioning
confidence: 98%
“…Dahle et al [14] and Barrett et al. [15] found no correlation between foot type and ankle sprains whereas Williams et al [16] reported a higher incidence of ankle sprains in individuals with a high arch.…”
Section: Introductionmentioning
confidence: 98%
“…12 Low cut footwear have a lower mass, whereas higher cut footwear are heavier but provide additional support. 12 Although the effects of high and low cut footwear in other sports have been investigated previously, [13][14][15] these effects have not been examined in American football.…”
Section: Introductionmentioning
confidence: 99%
“…Others state that high-top shoes are expected to lose their rigidity with wear, and that the benefits of high-top shoes in studies cited here may come from the newness of their materials vs. their height [35]. Because professional players may have the luxury of playing each game in new shoes whereas the casual or amateur player may not, findings from such studies may not be applicable to the everyday athlete [9].…”
Section: Range-of-motionmentioning
confidence: 92%
“…High-top shoes have been conventionally indicated for athletes who are convalescing from ankle injuries or may have increased ankle injury risk [6], or who play certain positions [7], given the footwear's presumed ability to limit ankle range-of-motion (ROM) [2,4]. Studies utilizing court footwear such as basketball shoes [6,[8][9][10] or volleyball shoes [11] have explored the possible relationships between shoe height, ROM, and/or injury risk utilizing both laboratory and clinical models but have yielded conflicting results.…”
Section: Introductionmentioning
confidence: 99%